Nanostructured spinel type cobalt oxides for electrochemical water splitting - Ramsundar, R. M. (CSIR - National Chemical Laboratory, Pune, 2018)
Due to the increased population and anthropogenic activities, the world energy demand keeps increasing and the energy supply is lesser than the demand. Currently, major part of the energy supply is from the fossil fuels which emits CO2 while burning and increases the global warming effect. Hydrogen is one of the fuels having high energy density than all other conventional fuels and it will give only water as a by-product while burning. Electrochemical water splitting is one of the attractive methods to produce hydrogen and it contains two half-cell reactions, hydrogen evolution at the cathode and oxygen evolution at the anode. Among these, oxygen evolution has sluggish kinetics and complicated multistep mechanism. At present, precious metal oxides such as RuO2 and IrO2 are used as anode materials for the oxygen evolution. To reduce the cost of production, the efficiency of the system has to be improved and the precious metal oxide catalysts have to be replaced by earth abundant and cost effective catalysts. Recently, Co3O4 is identified as one of the potential catalyst for the oxygen evolution due to its thermodynamic stability and electrocatalytic activity. In this thesis, we have studied the role of different oxidation states of cobalt in Co3O4 to increase the stability and electrocatalytic activity for the oxygen evolution reaction Chapter 1 is a general introduction on the importance and production of hydrogen, water splitting mechanism and the catalysts used for water splitting. It also gives a brief introduction to the oxygen evolution reaction, the catalysts used, mechanism and thermodynamic study of the catalyst for oxygen evolution, and role of oxygen evolution catalyst in artificial leaf. The factors which influence the electrocatalytic activity for the oxygen evolution reaction are discussed. The oxygen evolution catalysts based on cobalt and their electrocatalytic studies are discussed. Finally, the structure and properties of the spinel Co3O4 and its importance in the oxygen evolution reaction are discussed. Chapter 2 discusses about the synthesis of nanosized metal oxides by coprecipitation and autocombustion methods. Also, it discusses about the various characterization techniques used in the present study such as XRD, TEM, XPS, BET analysis and magnetic measurements. The details about the electrochemical methods like catalyst ink preparation, Tafel plot data collection and quantitative oxygen gas measurements are discussed. Chapter 3 discusses about the electrocatalytic activities of nanostructured Co3O4 synthesized by different methods. Co3O4 nanorods are synthesized by template free, simple coprecipitation/digestion method and the electrocatalytic activity in a wide pH range (4-14) is studied. The stability of Co3O4 nanorods in neutral and acidic pH is found to be enhanced due to the usage of phosphate buffer as electrolyte. The electrocatalytic activity of Co3O4 nanoparticles synthesized by autocombustion method are studied at basic pH and compared with the activity of Co3O4 nanorods. Both the Co3O4 nanorods and nanoparticles showed a low overpotential of 385 mV at 1 mA/cm2 at neutral pH. The electronic structure of Co3+ in both the Co3O4 nanostructures and their electrocatalytic activities are correlated. Chapter 4 discusses the role of Co2+ in the electrocatalytic activity of Co3O4 for the oxygen evolution reaction. Zn2+ is partially and progressively substituted for Co2+in Co3O4 and the structural and electronic properties are studied using various techniques. Zn-substitution in Co3O4,is found to increase the high-spin contribution Co3+in the octahedral sites as confirmed by absorption spectroscopy and magnetic studies. The population of high-spin Co3+ in the ZnxCo3-xO4 is correlated with the electrocatalytic activity for the oxygen evolution reaction and Zn0.8Co2.2O4gives the lowest overpotential (260 mV at 10 mA/cm2) at the basic pH medium and the reason behind the enhanced electrocatalytic activity is discussed. Chapter 5 discusses the role of Co3+ in the electrocatalytic activity of Co3O4 for the oxygen evolution reaction,by replacing Co3+ with Al3+. Al-substituted Co3O4 compositions are characterized using various techniques. The electrocatalytic activity studies on Co3-xAlxO4 showed that increasing the Al content decreases the electrocatalytic activity for the oxygen evolution reaction. It is confirmed that the reduction in the electrocatalytic activity is due to the decreased population of Co3+ in the compounds.. Chapter 6 discusses the effect of oxidation state of cobalt in the spinel cobalt oxides on the oxygen evolution reaction. Different oxidation states of cobalt (2+, 3+ and 4+) has been tuned in the cobalt oxides without changing the structure of the cobalt oxides. The electrocatalytic activity of Li0.5Co2.5O4 (only Co3+) is compared with that of Co3O4 (Co2+ and Co3+). In the same way, the activity of LiCoO2 (only Co3+) is compared with that of Li0.5CoO2 (Co3+ and Co4+). Finally, the electrocatalytic activities of Co3O4, Li0.5Co2.5O4, LiCoO2 and Li0.5CoO2are compared and correlated with the oxidation state of cobalt. Chapter 7 summarizes the work reported in the previous chapters and the various factors that influence the electrocatalytic activity of cobalt oxides for oxygen evolution reaction. Scope for future work on the studied materials is discussed.
Keywords: Cobalt Oxide; Water Splitting; Electrochemical Oxygen Evolution